Exploitation of a woody host plant and cerambycidassociated volatiles as hostfinding cues by the larger grain borer (Coleoptera: Bostrichidae) - Borgemeister, C.; Goergen, Georg E.; Tchabi, A.; Awande, S.; Markham, R.; Scholz, D. (Oxford University Press, 1998)
We collected twigs of Lannea nigritiana (Sc. Elliot) Keay attacked by the girdling cerambycid Analeptes trifasciata F. in the Lama forest of central Benin, West Africa. Emergence data from A. trifasciata wood samples revealed a diverse insect fauna, which consisted of 27 primarily coleopteran species of 8 different families. More than 70% of the identified insects were bostrichids. We report an association of the exotic larger grain borer, Pmstephanits tnmcatiis (Horn), and its introduced natural enemy, the histerid predator Teretriosoma nigrescens Lewis, with twigs girdled by an indigenous cerambycid. We found more P. truncatus directly above the girdling site than elsewhere. P. truncatus is not attracted to volatiles emitted by adults or larvae of A. trifasciata but is significantly attracted to odors of cerambycid frass, as well as to girdled and mechanically damaged L. nigritiana twigs. We discuss these results with regard to the host-finding behavior of P. truncatus.